Posterior Capsule Opacification (PCO) Cases at Lamongan Eye Clinic: Two Years of Retrospective Data - Irma Suryani; Uyik Unari (Vision Science and Eye Health Journal, 2022)
Introduction: Posterior capsular opacity (PCO) is the most common complication of cataract surgery. PCO is caused by the lens epithelial cells (LEC), which then proliferate in the capsular bag after surgery. Several complications can occur, such as increased intraocular pressure (IOP), cystoid macular edema (CME), retinal hemorrhage, retinal detachment, and implanted lens (IOL) damage. Capsule Nd:YAG laser is currently the standard procedure for treating PCO, with a success rate of 95%. Purpose: This study aimed to provide an overview of PCO incidence and the success rate of PCO handling in the eye clinic. Methods: This study was a retrospective observational study. Data was taken from medical records of patients diagnosed with PCO who came to the Lamongan Eye Clinic for two years (May 2018 to April 2020). Data regarding the profile of the subject was analyzed descriptively. The data distribution was tested using the Kolmogorov-Smirnov test. Results: From May 2018 to April 2020, 134 patients with PCO came to the Lamongan Eye Clinic. Mean pre-laser best-corrected visual acuity (BCVA) was 0.76 ± 0.44 (logMAR), post-laser was 0.40 ± 0.40 (logMAR). There was a significant difference in the mean refraction correction of the PCO patients before and after Nd:YAG laser capsulotomy, whereas the mean BCVA after undergoing YAG laser was higher than before. Mean pre-laser IOP was 15.00 ± 3.55 mmHg and post-laser was 14.20 ± 3.27 mmHg. The mean post-laser IOP was lower than the pre-laser IOP. The Nd:YAG laser capsulotomy significantly affected IOP. Conclusions: There is a statistically significant improvement in BCVA before and after capsulotomy. Capsulotomy had a significant effect on improving BCVA up to 7%; however, had no effect on IOP.